The effect of physical activity on depression in adolescence and emerging adulthood: A growth‐curve analysis. (23rd February 2015) - McPhie, Meghan L.; Rawana, Jennine S.
ABSTRACT: This study examined the influence of physical activity on the trajectory of depression from adolescence through emerging adulthood (EA). Using data from the National Longitudinal Study of Adolescent Health (Waves I to IV), latent growth curve modeling was performed to assess how physical activity and gender influenced depression across adolescence and EA. Higher levels of physical activity in mid‐adolescence were associated with lower levels of depression during mid‐adolescence and slower inclines and declines in depression over time. Boys had lower levels of depression in mid‐adolescence and slower inclines and declines in depression over time compared to girls. Findings provide evidence that current theories on understanding depression and mental health prevention programs may be enhanced by the inclusion of physical activity.